The demand for professional knowledge as a key factor of the development of outsourcing of financial and accounting services in Poland - Bagieńska, Anna (Business, Management and Economics Engineering, 2016)
The access to professional knowledge and specialists’ skills is possible for small enterprises thanks to the outsourcing of services. Purpose – The aim is to analyse the reasons for the outsourcing of accounting services and the factors influencing the choice of the accounting office. The specific aim is to evaluate the entrepreneur’s benefits resulting from using the knowledge of the specialists providing outsourcing services. Design/metodology/approach – A questionnaire survey was conducted among 120 entrepreneurs who outsource accounting services in the Podlaskie Region in Poland. Findings – The most important factors influencing the entrepreneur’s cooperation with the accounting office are: high quality of services resulting from the competence of the employees of the office, the range of services offered by the company, advising on finance management, correctness of tax accounting, the possibility of using additional services. Due to high competitiveness, the demand for professional knowledge influences the development of the outsourcing of financial and accounting services to a greater degree than the price of the services offered by the accounting offices.